Fragment późnośredniowiecznej akwamanili z Bobrownik, woj. włocławskie - Horbacz, Tadeusz J. (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
The author presents in this article a fragment of the cla y zoomorphic aguamanilla discovered in the castle at Bobrowniki (province of Włocławek) in 1978. This relic, being stylistically connected with the third group of clay figural vessels to be found in the area of Central Europe and analyzed recently by E. Kasten, the author dates back to mid-15th century and treats as a product from a local craftsman's shop. The aquamanilla from Bobrowniki is — in the author's opinion — a duplication of the Late-Mediaeval clay vessels the creation of which is most probably due to contacts with the German culture circle.